GROWTH AND YIELD RESPONSES OF SOYBEAN (Glycine max L.) TO ZINC OXIDE (ZnO) NANOPARTICLES FOLIAR APPLICATION - Fayomi Omotola Michael; Olasan Joseph Olalekan; Aguoru Celestine Uzoma; Terhemba Mamnenge Sarah (Biotechnologia Acta)
Aim. This study was purposed to investigate the effects of zinc oxide nanoparticles (ZnO NPs) on the growth and yield performance of two soybean (Glycine max L.) varieties, TGX1904-6F and TGX1951-3F, under controlled experimental conditions.